Characterization of cerulenin-resistant mutants of Candida albicans. - Hoberg, K A (1986)
Cerulenin, an inhibitor of fatty acid biosynthesis, has been used to study the role of the plasma membrane in germination of Candida albicans. To further elucidate this association, spontaneous, cerulenin-resistant mutants of C. albicans were isolated. Two of the mutants, 4918-2 and 4918-10, were compared biochemically with wild-type cells (4918). All strains grew equally well at 37 degrees C and synthesized fatty acids at comparable rates in the absence of the drug. In the presence of cerulenin, wild-type cells did not proceed through a logarithmic growth stage and exhibited a significantly impaired ability to incorporate [3H]acetate into newly synthesized lipid material. All strains were examined ultrastructurally. Alterations were observed in the membranous structures of cerulenin-treated wild-type cells. Such changes were not observed in cerulenin-treated mutant strains. Further examination of mutant strains revealed differences in cell wall protein and polysaccharide compositions when compared with those of wild-type cells. These apparent alterations in cell surface components may be correlated with the reduced abilities of mutant strains to adhere, in vitro, to mammalian cells.